2015
DOI: 10.1186/s12876-015-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of esophageal involvement in systemic sclerosis and morphea (localized scleroderma) by clinical, endoscopic, manometric and pH metric features: a prospective comparative hospital based study

Abstract: BackgroundSystemic sclerosis (SSc) is a generalized disorder of unknown etiology affecting the connective tissue of the body. It affects the skin and various internal organs. Gastrointestinal tract involvement is seen in almost 90% of the patients. Esophagus is the most frequently affected part of the gastrointestinal tract. Esophageal motility disturbance classically manifests as a reduced lower esophageal sphincter pressure (LESP) and loss of distal esophageal body peristalsis. Consequently, SSc patients may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 39 publications
1
27
0
5
Order By: Relevance
“…Its incidence rate is rare counting from 7% to 9% in total morphea patients. (Bielsa Marsol, ) Previous seldom cases have been reported that generalized morphea could accompany with organ dysfunction (Arif, Masood, Singh, & Hassan, ).…”
mentioning
confidence: 99%
“…Its incidence rate is rare counting from 7% to 9% in total morphea patients. (Bielsa Marsol, ) Previous seldom cases have been reported that generalized morphea could accompany with organ dysfunction (Arif, Masood, Singh, & Hassan, ).…”
mentioning
confidence: 99%
“…evaluated reflux parameters via ambulatory 24‐hour pH testing in 41 SSc patients, and found that 80.5% had abnormal results, with a mean AET of 8.5% . However, the study lacked impedance‐pH metry, which is the gold standard for the assessment of GERD . Furthermore, all patients were studied off PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Weakly acid reflux events 24 However, the study lacked impedance-pH metry, which is the gold standard for the assessment of GERD. 24 Furthermore, all patients were studied off PPI therapy.…”
Section: Acid Reflux Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthralgias and myalgias are common. Patients may develop dysphagia secondary to external compression (76). In the setting of normal CT scans, restrictive patterns have been observed on pulmonary function tests; attributed to external limitations of rib cage mobility (77).…”
Section: Introductionmentioning
confidence: 99%